Financial assets and instruments for mobilisation of saving - Lakdawala, Dansukhlal Tulsidas; Mody, R. J. (Ahmedabad : Bombay : Sardar Patel Institute of Economic and Social Research ; distributed by Popular Prakashan, 1975)
This research study aims at analyzing the interdependence between the growth of financial assets and mobilization of savings, and at examining the determinants of demand for certain financial assets. Effectiveness of various fiscal incentives for encouraging savings was also discussed.
Sponsored by the Research Programmes Committee of the Planning Commission, Govt. of India.
Includes bibliographical references and index.
usc 14/7/17
Loans
Keywords: Saving and investment; Saving and investment; Capital; India